Parathyroid hormone and parathyroid hormone-related protein - Nissenson, Robert (Henry Stewart Talks, 2007)
Relationship between PTH and PTHrP, Biological actions of PTH and PTHrP, Control of PTH secretion, Mechanisms of action of PTH and PTHrP, Clinical correlates
Reviewed at 2022/05/22